Application of LES-CFD for predicting pulverized-coal working conditions after installation of NOx control system. (1st October 2018) - Adamczyk, Wojciech P.; Isaac, Benjamin; Parra-Alvarez, John; Smith, Sean T.; Harris, Derek; Thornock, Jeremy N.; Zhou, Minmin; Smith, Philip J.; Żmuda, Robert
Abstract: The upcoming environmental requirements outlined at the 2017 European Commission Integrated Pollution Prevention and Control (IPPC) are becoming more and more strict in comparison to the existing standards – IED 2010/75/EU. Questions arise about changes in boiler operating conditions after the adoption of the regulations to fulfill specified emission limits. Of initial concern is the question of which technology to pursue in order to reach the specified level of NOx emissions at 150 mg/Nm 3 @6%O2 . By introducing an air staging technique the NOx limit can be partially achieved; however these changes affect the boiler operation in a detrimental way. In order to investigate impact of de-NOx installation on the temperature and heat flux distribution, numerical techniques can be used. In order to determine the impact of the changes in the boiler operation, this paper presents the application of an advanced, multiphase open-source code Arches, developed at the University of Utah for modeling pulverized-coal combustion using Large-Eddy Simulation (LES). Numerical simulations showed the effect on the boiler's working parameters e.g., heat-transfer rate, temperature distribution, species concentration, and NOx emission before and after proposed modifications. Graphical abstract: Image 1 Highlights: ARCHES CFD-LES code applied for modeling pulverized coal combustion process in midsize industrial boiler. Two air staging techniques for NOx control has been numerically investigated. Numerical results have been qualitatively and quantitatively compared to the HVT measurement data.